2020
DOI: 10.1042/bsr20200394
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine exerts neuroprotective effects during high glucose-induced neural injury by inhibiting miR-125b

Abstract: Diabetic neuropathy (DNP) is the most common complication of diabetes mellitus affecting approximately 50% of diabetes patients. Studying the effect of potential drugs with antioxidant properties and minimal toxicities on neural cells may lead to the development of new and safe pharmacotherapy. Dexmedetomidine (DEX), a highly selective α2-adrenoceptor agonist, is a clinically used sedative also known to have neural protection effect. In the present study, we aimed to investigate the protective role of DEX in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…36,37 In this study, qRT-PCR revealed that DEX alleviates H 2 O 2 -induced PC12 cell apoptosis, downregulates the expression of cleaved caspase-3, and upregulates the expression of Bcl-2. 31,34,38 Furthermore, this phenomenon could be reversed by the overexpression of miR-134, and HIBD pathology in neonatal rats and OGD-induced neuronal death in PC12 cells could be prevented by miR-134 inhibition. 28 Thus, these results indicate that H 2 O 2 -induced PC12 cell apoptosis can be inhibited by DEX by reducing miR-134 levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…36,37 In this study, qRT-PCR revealed that DEX alleviates H 2 O 2 -induced PC12 cell apoptosis, downregulates the expression of cleaved caspase-3, and upregulates the expression of Bcl-2. 31,34,38 Furthermore, this phenomenon could be reversed by the overexpression of miR-134, and HIBD pathology in neonatal rats and OGD-induced neuronal death in PC12 cells could be prevented by miR-134 inhibition. 28 Thus, these results indicate that H 2 O 2 -induced PC12 cell apoptosis can be inhibited by DEX by reducing miR-134 levels.…”
Section: Discussionmentioning
confidence: 98%
“…17 Furthermore, DEX exerted neuroprotective effects on PC12 cells under high glucose by regulating the miR-125b-5p/VDR axis. 31 Accumulating evidence suggests that oxidative stress induces inflammation and tissue damage. Notably, after LPS treatment, the levels of miR-134, IL-1b, and TNF-a were significantly increased in the hippocampus and cortex but decreased after DEX treatment, indicating…”
Section: Discussionmentioning
confidence: 99%
“…In PC12 cells with high glucose to induce DN, dexmedetomidine reduced ROS formation and neuronal 2A -adrenoceptor (Ma et al, 2004) apoptosis by inhibiting miR-125b-5p expression, which regulates gene expression related to apoptosis, autophagy, cell proliferation, metabolism, and survival. Dexmedetomidine also reduced neuronal apoptosis and oxidative stress by activating VDR expression, which involves neuronal function, inflammation, cell differentiation and immune regulation (Hou et al, 2020).…”
Section: Neuroprotective Effect Of Dexmedetomidine In Substance-induced Neuronal Injurymentioning
confidence: 95%
“…Another study showed that MALAT1 competitively binds to miR-125b against vascular endothelial-cadherin, which may promote neovascularization in diabetic retinopathy [81]. Although there is a lack of direct evidence showing MALAT1/ miR-125b axis affects oxidative stress, it is reported that ROS production in neuronal PC12 cells is remarkably upregulated upon transfection with the miR-125b-5p mimic under high-glucose conditions [82]. Whether the interaction between MALAT1 and miR-125b contributes to the redox homeostasis in diabetic retinopathy is worthy of investigation.…”
Section: Malat1mentioning
confidence: 99%